Increasing Student Interest in Interactive Multimedia Product Creation Subject through Scratch-Based Learning Media - Hana Romauli Sipahutar; Nurcahya Pradana Taufik Prakisya; Rosihan Ari Yuana (Informatics Education Department, Faculty of Teacher Training and Education, Universitas Sebelas Maret, 2024)
Engaging students is essential in education. If students are interested in a subject, they will study it repeatedly, driven by their intrinsic motivation to achieve a goal. However, one of the schools, SMK N 1 Demak, has experienced problems with students' interest in learning. A teacher stated that during lessons for the